Temperature dependence of critical current and transport current losses of 4 mm YBCO coated conductors manufactured using nonmagnetic substrate. Issue 1 (November 2015) - Kvitkovic, J; Hatwar, R; Pamidi, S V; Fleshler, S; Thieme, C
Abstract: The temperature dependence of the critical current and AC losses were measured on American Superconductor Corporation's (AMSC) second generation high temperature superconducting (2G HTS) wire produced by Rolling Assisted Biaxially Textured Substrate (RABiTS) and Metal Organic Deposition (MOD) process. Wires manufactured with two types of substrates were characterized. The magnetic substrate with composition Ni5a%W exhibits a magnetic signature and has non-negligible AC losses in AC power applications. A new nonmagnetic substrate with an alloy composition Ni9a%W has been developed by AMSC to address the AC losses in 2G HTS. The data presented show that the performance of the new conductor is identical to the conductor with magnetic substrate in terms of critical current density. The data on AC losses demonstrate the absence of ferromagnetic loss component in the new conductor and significantly reduced AC losses at low to moderate values of I/Ic. The reduced losses will translate into reduced capital costs and lower operating costs of superconducting electrical devices for AC applications.